(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Objective: Objectives:- To compare mean duration of bone union in traction followed by spica cast versus titanium elastic nailing (TEN) for fracture shaft of femur in children of age 6-12 years. Patients and Methods: This Randomized Control Trials was carried out in the Department of Orthopaedic Surgery, Nishter Hospital Multan from November 2013 to May 2014.A total of 60 patients were included in the study. Results: Out of 60 patients 31 (51.7%) were male and 29 (48.3%) were Female. As regard to the age of patients, male (31) were have mean age of 8.84 and Standard deviation was 2.035, similarly female (29) were have mean age of 8.97 and Standard deviation was 2.009. As regard to the outcomes group 1 with spica Casting were have mean duration 8.77 weeks and Standard deviation was 1.88. Similarly in-group 2 Titanium Elastic Nailing were have Mean of 11.99 weeks and Standard deviation was 20.303. After applying T-test P value calculated as P=.012 which is a valid value. Conclusion: According to this study TEN has better outcomes as compared to the traction followed by spica cast. Key words: Femur, Hip Spica, Titanium Elastic Nailing, and Femoral Shaft